Assessment of the cutaneous trunci muscle reflex in neurologically abnormal cats. Issue 12 (December 2020) - Paushter, Aaron M; Hague, Devon W; Foss, Kari D; Sander, William E
Objectives: The aim of this study was to evaluate the presence of the cutaneous trunci reflex (CTR) in a population of neurologically abnormal cats in regard to age, body condition score (BCS), sex, breed, evidence of traumatic injury, pain, known metabolic disease, mentation, neurolocalization and diagnostic classification. Methods: A retrospective medical record review was performed to identify cats with a history of neurologic disease undergoing a complete neurologic assessment between 24 September 2012 and 20 March 2019. CTR outcome (present, absent), signalment, evidence of traumatic injury, pain, known metabolic disease, mentation, neurolocalization and diagnostic classification were recorded. Results: A total of 182 cats were identified. The CTR was present in 118 cats (64.8%) and absent in 64 cats (35.2%). Statistical analysis revealed no association between CTR outcome and age, BCS, sex, breed, evidence of traumatic injury, non-spinal pain, known metabolic disease, mentation, neurolocalization or diagnostic classification. A significant association was found between spinal pain and CTR outcome ( P  = 0.037). Conclusions and relevance: These findings suggest that elicitation of the CTR in the cat can be unreliable. Further prospective controlled studies are warranted to determine whether continued inclusion of the CTR in feline neurologic examinations is justified. Consideration of the reliability of the CTR is indicated, particularly in the context of fractious or anxious patients for which only a limited window for examination may be present.